A full thickness and partial rotator cuff tear with retraction of fibers and reconstruction with palmaris longus graft - Basha, Mulla Saddar; Dharani, N V Naga (Indian Journal of Case Reports, 2024)
The report mainly appraises full-thickness tears at myotendinous junctions which are rare and only described in the supraspinatus and infraspinatus muscles. There is very little literature describing both tears occurring concurrently. After suffering mechanical damage to her shoulder, a 64-year-old woman was examined for pain in the shoulder on movement; the patient underwent radiographic and clinical evaluation which revealed full-thickness rotator cuff tears with retraction of fibers. Hence, the plan of care is to offer the best surgical techniques to guarantee a good result and a quick recovery. A full-thickness tear at the myotendinous junctions of the supraspinatus tear and partial tear at the subscapularis tendon and infraspinatus tendon at humeral attachment was confirmed radiographically in this case. To make a diagnosis, a high level of clinical suspicion must be supported by specific magnetic resonance imaging characteristics.